Identification of Antioxidant Compounds Structure Large-Leafed Mangrove Fruit - Nurjanah Nurjanah; Agoes Mardiono Jacoeb; Sabri Sudirman (Jurnal Pengolahan Hasil Perikanan Indonesia, 2016)
Antioxidants are compounds that can inhibit or prevent the oxidation of the easily oxidized substrate.One of the plants as a potential source of bioactive compounds and antioxidant activity is large-leafedmangrove (Bruguiera gymnorrhiza). This plant is commonly found in the Pacific region of Southeast Asia,Ryukyu Islands, Micronesia and Polynesia (Samoa) to subtropical regions of Australia and has been usedby the society. This study aimed to determine the bioactive compounds structure of large-leafed mangrovehas the highest antioxidant activity. The compound structure prediction was done by Nuclear MagneticResonance (NMR). The compound structure in the selected antioxidant fractions are flavonol, glikosilfalvonand flavon. Those three compounds are flavonoid compound which has a great role as the one that hasantioxidant activity in large-leafed mangrove fruit.